PENGARUH PENGENCERAN MEDIA DASAR TERHADAP PERTUMBUHAN KULTUR JAHE DALAM PENYIMPANAN SECARA IN VITRO - SITTI FATIMAH SYAHID; NURLIANI BERMAWIE (Jurnal Penelitian Tanaman Industri, 2000)
Effect of dilution of basic medium on ginger growth during conservation in vitroBasic medium dilution could affect the growth of the culture. The effect of basic medium dilution was evaluated at the laboratory of Research Institute for Spices and Medicinal Crops from October 1998 to June 1999. Sterile shoots of ginger were used as ex plants. Basic medium dilution from 3/4 MS, 1/2 MS, 1/4 MS and MS normal (control) were used as treatments. The media were enriched with BA 3 mg/1 and Sucrose 6%. The treatments wee arranged in a completely randomized design with three eplications. Results showed that all the dilution treatments inhibited the grow of the culture during live months of conservation period, especially on 1/4 MS + BA 3 mg/1 + Sucrose 6% . On the media, the number of shoots wee 3.55. Based on cultue performance the best medium for conservation was 1/2 MS + BA 3 mg/1 + Sucrose 6%. All of the culture was able to growth in regeneration media after they were conserved for ive months. Results of this experiment could be applied in reducing sub-cultue frequency to a new media and maintain the culture stability. e